Natural Capital Accounts and Policy in Indonesia - World Bank (World Bank, Washington, DC, 2019)
Indonesia is a diverse archipelago nation of more than 300 ethnic groups and has the largest economy in Southeast Asia as well as notable economic growth since overcoming the Asian financial crisis of the late 1990s. The World Bank led Wealth Accounting and the Valuation of Ecosystem Services Partnership (WAVES) worked with the Government from 2015 to 2019 to strengthen SISNERLING, focusing on land and ecosystem accounting.26 The results and lessons learned of this long-term engagement are reported in this document, and the full body of work produced by WAVES will be made available online and provide input for future analysis. The report has five sections, including this introductory section. Section two provides information on the environmental and economic development in Indonesia, in context of wealth and natural capital, and how NCA has been embraced by the Government of Indonesia. Section three focuses on results from the developed natural capital accounts, while section four reveals the impact of NCA in policy and planning and section five describes the way forward. The references and annexes follow on from these sections.